The Role of the North Sumatra Regional Police in Disclosing Narcotics Crimes - Haris Putra Utama Limbong; Yasmirah Mandasari Saragih; Tamaulina Br. Sembiring (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Narcotics are substances or drugs derived from plants or non-plants, either synthetic or semi-synthetic, which can cause decreased or altered consciousness, loss of feeling, reduced or even eliminated pain, and can cause dependency. Drug abuse in Indonesia has reached a very worrying stage. Drugs no longer recognize age limits , old people, young people, teenagers and even children are users and dealers of illegal drugs. The illegal distribution of drugs in Indonesia is no less worrying, drugs are not only circulating in big cities in Indonesia, but have also penetrated into small areas. The problem raised in this study is the role of the North Sumatra regional police in uncovering narcotics crimes. The type of research used is empirical legal research with conceptual approach methods, legislative approaches, and sociological approaches. The types of data are primary data and secondary data, while the data sources for this study come from the results of interviews with respondents and informants. It was concluded that the role of the North Sumatra Regional Police in disclosing narcotics crimes is that the police conduct counseling in schools, install banners, pamphlets on the highway, carry out patrols and police operations. Furthermore, the police enforce the law starting from the investigation stage to the transfer of cases to the District Court while still referring to Law No. 2 of 2002 concerning the Police and other related regulations. The obstacles faced by the North Sumatra Regional Police are: Community factors, Limited Human Resources, Limited operational funds and Law enforcement factors .